Profiling Junior High School Students with Pancasila Values through Life Skill-Based Literacy - Arifin, Muhammad; Chaniago, Edi Salim; Ekayati, Rini (International Journal of Social and Management Studies, 2023)
Building the students’ characters based on the profile of Pancasila is the vision of education in Indonesia. This research focuses on implementing the profile of Pancasila students through life skills-based literacy at SMP Negeri 14 Binjai. This study aims to describe the application of life skills-based literacy in shaping the profile of Pancasila students at a junior high school in Binjai. The method applied in this research is action research with four stages, namely planning, implementation, observation and evaluation, and reflection. This research has produced the following findings: 1) The application of life skills-based literacy can form a profile of Pancasila students who are characterized by faith, piety to God Almighty, noble character, critical reasoning, cooperation, creativity, independence, and global diversity, 2) The implementation of digital literacy, cultural literacy, scientific literacy, and literacy comprehensively and measurably can improve student achievement, both in academic and non-academic fields,and 3) The application of a productive smart veranda has resulted in students' skill products in the form of crafts made from candles, dish soap, and woven bamboo that can equip them to be confident and independent. Life skills-based literacy activities as an effort to form a profile of students with Pancasila values who believe, and fear God Almighty, and have a noble character, critical reasoning, creativity, independence, cooperation and global diversity.